Application of Computer Network Technology in Social Insurance Fund Supervision and statistics - Li, Junjie (Journal of Theory and Practice of Social Science, 2023)
With the development and progress of society, there are more and more industries in life, people's work has become diverse, and the workload is more and more heavy. However, the rapid development of computer network technology has brought great convenience to people, changed the way people used to work, improve people's work efficiency, since then people realize the arrival of office automation. In this paper, combined with the author's many years of working experience, how to better apply the computer network technology in the social insurance fund supervision and statistics work, launched a brief analysis.